Advances in Exploration of Dark Energy - Jöge, Friedhelm M. (European Journal of Applied Sciences, 2024)
The Foundation of a Dark Energy Theory is formulated and laid. Based on the article „Calculation of Dark Energy and Dark Matter“ [1] in particular a formula is derived and used to exact calculation of Dark Energy. The theoretical result is confronted with the numerical value calculated from the MAX PLANCK Institut for Radio Astronomy. Excellent matching of numerical value resulting in three independent paths make the formula plausible.